Antimicrobial Peptides: Bringing Solution to the Rising Threats of Antimicrobial Resistance in Livestock - Saeed, Shamsaldeen Ibrahim; Mergani, AhmedElmontaser; Aklilu, Erkihun; Kamaruzzaman, Nor Fadhilah (Frontiers in Veterinary Science, 2022)
Antimicrobial therapy is the most applied method for treating and preventing bacterial infection in livestock. However, it becomes less effective due to development of the antimicrobial resistance (AMR). Therefore, urgent need to find a new antimicrobial to reduce the rising rate of AMR. Recently Antimicrobial peptides (AMPs) have been receiving increasing attention due to their broad-spectrum antimicrobial activity, rapid killing activities, less toxicity, and cell selectivity. These features make them potent and potential alternative antimicrobials to be used in animals. Here we discuss and summarize the antimicrobial peptides in animals, classification, structures, mechanisms of action, and their potential use as novel therapeutic alternative antimicrobials to tackle the growing antimicrobial resistance threats.